The Interaction between Service Quality and Students Satisfaction - Ahmad, Sheikh Aftab (Journal of Education and Vocational Research, 2018)
This study aims to describe the effect of service quality on students’ satisfaction. The study used a sample of respondents from university students in Hail, Saudi Arabia, and the data were collected through questionnaire. Descriptive and regression analysis were used to find out the relationship between students satisfaction and service quality. This study concluded that there is a significant effect of tangible, reliability on students’ satisfaction at university in Hail state. Moreover, there is a difference in service quality of higher educations managed by government and those managed by a foundation (private). Also, there is a difference between students satisfaction in public and private universities. Based on the findings, it is suggested that the government needs to pay more attention to increase service quality for the satisfaction of students, which will develop the public interest to go to university.